PENGARUH LINGKUNGAN KERJA DAN MOTIVASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. CATUR KARDA DEPO BANGUNAN SERPONG TANGERANG SELATAN - Tifanny Priescilia Kaitjily; Mutmainnah, Mutmainnah (Cahaya Ilmu Bangsa, 2024)
The purpose of this research is to determine the influence of the work environment and motivation on work productivity at PT. Catur Karda Depo Gedung Serpong South Tangerang partially and simultaneously. The method used is causal associative with quantitative techniques. The research population was 160 people. The sampling technique used the Slovin formula with results of 62 respondents. The data analysis used is validity test, reliability test, classical assumption test, descriptive analysis, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The research results show that the Work Environment partially has a significant positive effect on Work Productivity with a coefficient of determination value of 66%. Hypothesis testing results obtained t count > t table, namely 10.861 > 1.672. Likewise, motivation partially has a significant positive effect on work productivity with a coefficient of determination of 81%. Hypothesis testing results obtained t count > t table, namely 16.068 > 1.672. Work Environment and Motivation simultaneously also have a significant effect on Work Productivity with a coefficient of determination value of 81%. The results of the multiple regression equation are Y = 4.203 + 0.035 + 0.939. Hypothesis testing obtained a calculated F value > F table, namely 128, 414 > 3.15, so it can be said that H0 is rejected and Ha is accepted, which means that there is a positive and significant influence of the Work Environment and Motivation simultaneously on Work Productivity at PT. Catur Karda Depot Building Serpong South Tangerang.